The internationalisation of stockmarkets : the trend towards greater foreign borrowing and investment - Ayling, D. E. (Aldershot, Hants, England ; Brookfield, Vt. : Gower, 1986)
The book provides a comprehensive insight into the structural changes occurring in the world's money and capital markets.
Includes bibliographies and index.
osc 16/08/2018
Loans
Keywords: Stock exchanges; Capital market; Capital movements